An algebra problem by A Former Brilliant Member

Algebra Level 2

A function f ( x ) f(x) satisfies f ( x f ( y ) ) = f ( f ( y ) ) + x f ( y ) + f ( x ) 1 f(x-f(y))=f(f(y))+xf(y)+f(x)-1 for all x x and y y . If f ( 1 ) = 0 f(1)=0 , find the constant term in f ( x ) f(x) .


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let denotes the functional equation by P ( x , y ) P(x,y) as follows. We need to find the constant term of f ( x ) f(x) or f ( 0 ) f(0) .

P ( x , y ) : f ( x f ( y ) ) = f ( f ( y ) ) + x f ( y ) + f ( x ) 1 P ( 0 , x ) : f ( f ( x ) ) = f ( f ( x ) ) + f ( 0 ) 1 P ( 0 , 1 ) : f ( f ( 1 ) ) = f ( f ( 1 ) ) + f ( 0 ) 1 Note that f ( 1 ) = 0 f ( 0 ) = f ( 0 ) + f ( 0 ) 1 f ( 0 ) = 1 \begin{array}{ll} P(x,y): & f(x-f(y)) = f(f(y)) + xf(y) + f(x) - 1 \\ P(0,x): & f(-f(x)) = f(f(x)) + f(0) - 1 \\ P(0,1): & f(-{\color{#3D99F6} f(1)}) = f({\color{#3D99F6} f(1)}) + f(0) - 1 & \small \color{#3D99F6} \text{Note that }f(1) = 0 \\ & f({\color{#3D99F6} 0}) = f({\color{#3D99F6} 0}) + f(0) - 1 \\ \implies & f(0) = \boxed 1 \end{array}

Richard Desper
May 2, 2019

The question asks for "the constant term", which I'm taking to mean f ( 0 ) f(0) .
Let x = 0 , y = 1 x = 0, y = 1 .

Since f ( y ) = 0 f(y) = 0 , x f ( y ) = x x - f(y) = x . Thus f ( 0 ) = f ( 0 f ( 1 ) ) f(0) = f(0-f(1)) .

By the given relationship: f ( 0 f ( 1 ) ) = f ( f ( 1 ) ) + 0 f ( 1 ) + f ( 0 ) 1 f(0 - f(1)) = f(f(1)) + 0f(1) + f(0) - 1 = f ( 0 ) + 0 + f ( 0 ) 1 = f(0) + 0 + f(0) - 1 .

In summary f ( 0 ) = 2 f ( 0 ) 1 f(0) = 2f(0) - 1 , i.e. f ( 0 ) = 1 f(0) = 1 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...